Symbolism and Irony in Ernest Hemingway’s Hills like White Elephants a Feminist Approach - Ahmed, Shene Mohammed (Sulaimani Journal for Humanities, 2022)
In this paper, the woman protagonist in Ernest Hemingway’s Hills like White Elephant is discussed from a feminist point of view, how the male character tries to possess her thoughts and decisions. Furthermore, the text contains different symbols that are indirectly related to the life of the couple and the female’s decision, in addition to the irony in the male character’s speech. This paper is important in the sense that it explores the issue of gender with reference to the female protagonist. The paper also represents her difficult situation, for she is no ruler of her thoughts but rather the man is. It presents how certain objects and words that have shallow meanings can hold deeper and efficient connotations.
Keywords: Feminism; Irony; Symbolism; gender